2014
DOI: 10.1038/ncomms4975
|View full text |Cite
|
Sign up to set email alerts
|

Two-way traffic of glycoside hydrolase family 18 processive chitinases on crystalline chitin

Abstract: Processivity refers to the ability of synthesizing, modifying and degrading enzymes to catalyse multiple successive cycles of reaction with polymeric substrates without disengaging from the substrates. Since biomass polysaccharides, such as chitin and cellulose, often form recalcitrant crystalline regions, their degradation is highly dependent on the processivity of degrading enzymes. Here we employ high-speed atomic force microscopy to directly visualize the movement of two processive glycoside hydrolase fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 34 publications
2
83
0
1
Order By: Relevance
“…6, it is also assumed that there is no enzyme release from the ES complex after product formation. This assumption is supported by the fact that the measured values of processivity for Cel7A (18,27) and ChiA (65,66) are much lower than the degree of polymerization of the substrate, meaning that the release of enzyme by complete hydrolysis of the polymer chain is unlikely. The trapped-enzyme complex (E*ST) (Fig.…”
Section: C-cnw Hydrolysis (Equation 1)supporting
confidence: 48%
See 1 more Smart Citation
“…6, it is also assumed that there is no enzyme release from the ES complex after product formation. This assumption is supported by the fact that the measured values of processivity for Cel7A (18,27) and ChiA (65,66) are much lower than the degree of polymerization of the substrate, meaning that the release of enzyme by complete hydrolysis of the polymer chain is unlikely. The trapped-enzyme complex (E*ST) (Fig.…”
Section: C-cnw Hydrolysis (Equation 1)supporting
confidence: 48%
“…In trying to determine the k cat value from the "initial" rates, one needs first to define k cat . If Ϫ1 derived from the average speed of the movement of ChiA along ␤-chitin in a recent single -molecule tracking HS-AFM study (65). The consistency between the k cat values found from HS-AFM measurements and V max /[E OA ] max is expected because HS-AFM tracks only the actively moving complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly these figures are far lower than P Intr values of 4000 and 560 measured on bacterial cellulose and amorphous cellulose, respectively (17). Experimentally measured P app values for ChiA range between 5 and 30, depending on the substrate and the method used for measuring (40,(57)(58)(59). Therefore, the large discrepancy between P app and P Intr seems to hold also for ChiA.…”
Section: Discussionmentioning
confidence: 57%
“…The crystal structure of OfChtI gave structural evidence that ChtI has a long and open-ended substrate binding cleft with symmetrically distributed subsites that is believed to be a structural characteristic of an endo-acting chitinase (44). According to a structure-based sequence alignment, we found that Chi-h does not contain such a substrate binding cleft but contains a long substrate binding cleft with asymmetrically distributed subsites, a structural characteristic of the processive exo-acting chitinase SmChiA from Serratia marcescens (45). Thus, it is unlikely that Chi-h would be able to act through the same mode of action as ChtI.…”
mentioning
confidence: 98%